Eosinophilic gastrointestinal disorders and allergen immunotherapy: Lights and shadows. Issue 5 (27th February 2021) - Votto, Martina; De Filippo, Maria; Caminiti, Lucia; Carella, Francesco; de Castro, Giovanna; Landi, Massimo; Olcese, Roberta; Vernich, Mario; Marseglia, Gian Luigi; Ciprandi, Giorgio; Barberi, Salvatore
Abstract: Allergic diseases, such as IgE‐mediated food allergy, asthma, and allergic rhinitis, are relevant health problems worldwide and show an increasing prevalence. Therapies for food allergies are food avoidance and the prompt administration of intramuscular epinephrine in anaphylaxis occurring after accidental exposure. However, allergen immunotherapy (AIT) is being investigated as a new potential tool for treating severe food allergies. Effective oral immunotherapy (OIT) and epicutaneous immunotherapy (EPIT) induce desensitization and restore immune tolerance to the causal allergen. While immediate side effects are well known, the long‐term effects of food AIT are still underestimated. In this regard, eosinophilic gastrointestinal disorders (EGIDs), mainly eosinophilic esophagitis, have been reported as putative complications of OIT for food allergy and sublingual immunotherapy (SLIT) for allergic asthma and rhinitis. Fortunately, these complications are usually reversible and the patient recovers after AIT discontinuation. This review summarizes current knowledge on the possible causative link between eosinophilic gastrointestinal disorders and AIT, highlighting recent evidence and controversies.